2018
DOI: 10.1002/glia.23467
|View full text |Cite
|
Sign up to set email alerts
|

Prokineticin‐2 promotes chemotaxis and alternative A2 reactivity of astrocytes

Abstract: Astrocyte reactivity is disease- and stimulus-dependent, adopting either a pro-inflammatory A1 phenotype or a protective, anti-inflammatory A2 phenotype. Recently, we demonstrated, using cell culture, animal models and human brain samples, that dopaminergic neurons produce and secrete higher levels of the chemokine-like signaling protein Prokineticin-2 (PK2) as a compensatory protective response against neurotoxic stress. Since astrocytes express a high level of PK2 receptors, herein, we systematically charact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 74 publications
1
87
2
Order By: Relevance
“…Recently, Neal et al [ 162 ] discovered that PK2(prokineticin 2)-induced astrocyte reactivity leads to an increase in antioxidant and anti-inflammatory proteins with increasing glutamate uptake resulting in decreased inflammatory factors. Furthermore, Ma and colleagues [ 163 ] whilst working on SAH (subarachnoid haemorrhage)-induced early brain injury added that administration of rPK2 (recombinant PK2) or augmenting PK2 expression may stimulate a modulation of astrocytic polarisation towards a more protective (A2-type) phenotype.…”
Section: Cellular Subtypesmentioning
confidence: 99%
“…Recently, Neal et al [ 162 ] discovered that PK2(prokineticin 2)-induced astrocyte reactivity leads to an increase in antioxidant and anti-inflammatory proteins with increasing glutamate uptake resulting in decreased inflammatory factors. Furthermore, Ma and colleagues [ 163 ] whilst working on SAH (subarachnoid haemorrhage)-induced early brain injury added that administration of rPK2 (recombinant PK2) or augmenting PK2 expression may stimulate a modulation of astrocytic polarisation towards a more protective (A2-type) phenotype.…”
Section: Cellular Subtypesmentioning
confidence: 99%
“…In that case, selectively killing or reprogramming harmful activated astrocytes, and increasing the number of beneficial activated astrocytes, may also be effective approaches to ameliorate NDs. The proinflammatory effect of A1 has been confirmed in many studies (Clark et al, 2019;Li et al, 2018;Wang et al, 2018;Yun et al, 2018;Zou et al, 2019), while A2 is relatively few (Atsushi et al, 2018;Neal et al, 2018). Given that the hypothesis of two types of astrocyte is based on a single animal model, do these two subtypes play the same role in different diseases?…”
Section: Subtypes Of Activated Astrocytesmentioning
confidence: 97%
“…A recent study showed that activated (pro-in ammatory) microglia induce a neurotoxic A1 subtype of astrocytes, which secrete a currently unknown neurotoxin that results in neuronal cell death (48). A1 astrocytes can be discriminated from the neuroprotective A2 astrocytes not only by the upregulation of genetic markers (47)(48)(49)55), but also by distinct morphological changes, which appear to be similar to those of microglia during neuroin ammation (56). While retraction of astrocytic processes, hypertrophy and gliosis has been described for astrocytes under various conditions (57), no study -to the best of our knowledge -comprehensively addressed alterations in astrocyte morphology during chronic neuroin ammation using a three-dimensional reconstruction pro ler.…”
Section: Hf Induces a Morphological A1 Astrocyte Phenotype In Both Pvmentioning
confidence: 99%